The Effect of Splint Dressing Training on Knowledge of Fracture Management in PMR Members at Vocational Schools in Makassar City - Ernasari Ernasari; Cahyono Kaelan; Andi Armyn Nurdin (An Idea Health Journal, 2021)
Balut bidai training aims to minimize the impact that can occur so that every lay person can help if they find victims who have an accident.The research aimed to analyze to what extent the effect of the splint wrap training using the watching video method on the fracture management knowledge of the Youth Red Cross members. This was the qualitative research with the one group pretest posttest design method with the samples of 70 students of YRC members. The samples were selected using the non-probability sampling technique with the purposive sampling approach. The date were analyzed using T-Test. The research result indicates that there is no significant difference concerning the knowledge level between the simulation group and video group (? = 0.063), whereas on the skill level, there is the significant difference between the simulation group and video group (? = 0.000). Thus, it can be concluded that the training using the video method can improve the fracture management knowledge fester than the training using the simulation method, so that it is expected that the training using the video method can be utilized for almost all topics, and every cognitive, affective, psychomotoric and interpersonal domain.